2011
DOI: 10.1021/jz200490h
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate for Debye–Waller Factors from Dynamic Stokes Shifts

Abstract: We show that the short-time behavior of time-resolved fluorescence Stokes shifts (TRSS) are similar to that of the intermediate scattering function obtained from neutron scattering at q near the peak in the static structure factor for glycerol. This allows us to extract a Debye-Waller (DW) factor analog from TRSS data at times as short as 1 ps in a relatively simple way. Using the time-domain relaxation data obtained by this method we show that DW factors evaluated at times ≥ 40 ps can be directly influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Specifically, the generalized localization model (GLM) of supercooled liquid dynamics, rather than attempting to directly model the temperature‐dependence of τ α on T , as does the Adam–Gibbs theory, focuses on understanding the relationship between τ α and high‐frequency rattling dynamics as quantified by the Debye–Waller factor 〈 u 2 〉. In terms of experimental applicability, this is an attractive theoretical framework because both τ α and 〈 u 2 〉 are experimentally accessible quantities; the former can be measured via neutron scattering and dielectric spectroscopy, for example, and the latter via neutron scattering, Mossbauer scattering, and time‐resolved Stokes‐shift spectroscopy . The GLM specifically predicts that these two quantities are related through the equation: τα=τnormalAexptrue[true(uA2true〈u2true〉true)α/21true] where τ A and unormalA2 are the values of τ α and 〈 u 2 〉 at the onset temperature T A of glass formation and α is a fitting parameter that within the GLM is interpreted as being related to the anisotropy of local segmental rattle volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the generalized localization model (GLM) of supercooled liquid dynamics, rather than attempting to directly model the temperature‐dependence of τ α on T , as does the Adam–Gibbs theory, focuses on understanding the relationship between τ α and high‐frequency rattling dynamics as quantified by the Debye–Waller factor 〈 u 2 〉. In terms of experimental applicability, this is an attractive theoretical framework because both τ α and 〈 u 2 〉 are experimentally accessible quantities; the former can be measured via neutron scattering and dielectric spectroscopy, for example, and the latter via neutron scattering, Mossbauer scattering, and time‐resolved Stokes‐shift spectroscopy . The GLM specifically predicts that these two quantities are related through the equation: τα=τnormalAexptrue[true(uA2true〈u2true〉true)α/21true] where τ A and unormalA2 are the values of τ α and 〈 u 2 〉 at the onset temperature T A of glass formation and α is a fitting parameter that within the GLM is interpreted as being related to the anisotropy of local segmental rattle volume.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, recent results have indicated that τ α is related to the Debye–Waller factor 〈 u 2 〉, a measure of picosecond‐timescale segmental rattling, via a universal relationship predicted by the generalized localization model (GLM) of supercooled liquid dynamics . Unlike the CRRs underlying the AG theory, 〈 u 2 〉 is experimentally quantifiable via methods including incoherent neutron scattering, Mossbauer scattering, and time‐resolved Stokes‐shift experiments . As such, any theory elucidating the relationship between 〈 u 2 〉 and relaxation dynamics in ionomers would provide a particularly useful framework for ionomer understanding and design.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that a surrogate for <u 2 > from neutron scattering could be found in signatures of time-dependent fluorescence from a probe molecule located within the formulation of interest [92]. However, technical challenges prevented this method from being used for powder samples.…”
Section: Dynamic Considerationsmentioning
confidence: 99%
“…The success of ⟨ u 2 ⟩ as a measure of the softness of confinement can be understood based upon a general scaling relationship between ⟨ u 2 ⟩, which is an experimentally accessible measure of local segmental rattle space on a picosecond timescale, and the high‐frequency shear modulus, G kT/(u2) . In essence, this result indicates that the dynamics of near‐interface polymers are more sensitive to interfacial energy when they are confined by a material exhibiting a relatively high glassy modulus.…”
Section: Introductionmentioning
confidence: 99%